Mencetak Pemimpin Masa Depan: Peran Pendidikan Agama Islam dan Psikologi Pembelajaran dalam Meningkatkan Kompetensi Guru - Jazila, Awatif Izza; Nikmah, Ma’rifatun; Prasetyo, Muhammad Diaz (QuranicEdu: Journal of Islamic Education, 2024)
Islamic Education (PAI) instills moral and spiritual values ??that are essential for leadership. Learning psychology, on the other hand, equips teachers with the knowledge and skills to create effective and student-centered teaching and learning processes. These two disciplines complement and strengthen each other in an effort to produce future leaders. Teachers who are skilled in learning psychology will be able to help students develop their potential to the maximum and become competent leaders in the future. This study aims to reveal the role of PAI and learning psychology in improving teacher competence. The researchers used qualitative research with a literature review type. The study results revealed that both PAI and learning psychology emphasize the importance of character development. Therefore, this study emphasizes that PAI and learning psychology have a very important role in producing future leaders through improving teacher competence in guiding and teaching students.